Psychological Well‐being in First‐ to Fifth‐Graders in the Context of Contemporary Social Situation of Development - Alla Andreeva; Olga Moskvitina (Вопросы образования, 2019)
Psychological well-being of children in elementary school and during the transition to middle school is analyzed in the sociocultural context of the post-industrial society from the perspective that Russian psychology has on the social situation of development, its objective and subjective components, and its influence on school students’ educational outcomes and mental health. Level of aspiration, self-esteem and age satisfaction serve as integral indicators of students’ psychological well-being in this study, providing the basis for judging whether the social situation of development meets children’s age-specific needs. The method of comparative-historical research allows observing the dynamics of a child’s psychological life as a function of the social situation of development. It is shown that the age structure of both self-esteem and the level of aspiration in contemporary first to fifth-graders differs dramatically from that of their age-mates observed in studies of the last quarter of the 20th century, while age satisfaction has remained positive throughout the age period analyzed. Age crises adequate to the current social situation of development are found to bring down all the analyzed parameters of school students’ psychological well-being in Grade 4, which then rebound in Grade 5. The findings illustrate psychological well-being of contemporary school students in the context of the drastically changing social situation of development of the post-industrial society. Some gender differences have been observed in psychological readiness for middle school. The temporal structure of age satisfaction shows that girls prefer retaining their familiar social position in the teacher–student system, while boys experience the end of elementary school as a crisis of relationship that cannot foster their personal development anymore.